Single-Cell Transcriptional Profiling of Cells Derived From Regenerating Alveolar Ducts - Ysasi, Alexandra B.; Bennett, Robert D.; Wagner, Willi; Valenzuela, Cristian D.; Servais, Andrew B.; Tsuda, Akira; Pyne, Saumyadipta; Li, Shuqiang; Grimsby, Jonna; Pokharel, Prapti; Livak, Kenneth J.; Ackermann, Maximilian; et al. (Frontiers in Medicine, 2020)
Lung regeneration occurs in a variety of adult mammals after surgical removal of one lung (pneumonectomy). Previous studies of murine post-pneumonectomy lung growth have identified regenerative "hotspots" in subpleural alveolar ducts. To isolate single cells from alveoloar ducts from post-pneumonectomy day 1, 3 and 7 mice, we used laser microdissection, enzymatic digestion and microfluidic isolation. Single-cell transcriptional analysis of the mice was performed using the C1 integrated fluidic circuit (Fluidigm) and a custom PCR panel designed for lung growth and repair genes. The multi-dimensional data set was analyzed using visualization software based on the tSNE algorithm (viSNE, Cytobank). The analysis identified 6 clusters; 1 cluster was present only after pneumonectomy. This post-pneumonectomy cluster was significantly less transcriptionally active than 3 other clusters and may represent a transitional cell population. The projection of bulk transcriptional data provided a provisional cluster identity for 4 of the 6 clusters. The transcriptional pattern of the 6 clusters was analyzed for genes associated with lung repair, matrix production and angiogenesis. The data demonstrated that multiple cell types (clusters) transcribed genes linked to these basic functions. We conclude that the coordinated gene expression across multiple clusters is likely a response to a shared regenerative microenvironment within the subpleural alveolar ducts.